Locale-varying relationships between tourism development and retail property prices in a shopping destination - Yang, Linchuan; Chau, K. W.; Lu, Yi; Cui, Xu; Meng, Fanyu; Wang, Xu (International Journal of Strategic Property Management, 2020)
Existing literature has inadequately examined the nexus between tourism and property prices. Additionally, it mainly focuses on hotels and housing, thereby overlooking other property categories (e.g., retail properties). The relationship between tourism development and retail property prices in shopping destinations (e.g., Hong Kong and Singapore) may hinge on the locale. More specifically, the relationship may be different in the tourist precinct or popular tourism shopping area (PTSA) and the unpopular tourism shopping area (UTSA). This study examines locale-varying relationships between tourism development (measured by tourist volume and tourism expenditure) and retail property prices from 2002Q1 to 2014Q4 in Hong Kong using standard and error-correction-model-based (ECM-based) Granger causality tests. Results of standard Granger causality tests indicate that tourism development Granger causes the increase in retail property prices in the PTSA but not in the UTSA. Moreover, results of ECM-based Granger causality tests further verify the robustness and plausibility of the tourism-led growth (in retail property prices) hypothesis in the PTSA. In other words, we find that tourism development measures can be used to better predict changes in retail property prices in the PTSA than simply referring to the price history.